2015
DOI: 10.1080/19393210.2015.1102974
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide in a fried potato dish (rösti) from restaurants in Zurich, Switzerland

Abstract: Rösti, a fried potato product, is a large contributor to acrylamide exposure locally in Switzerland. A survey of 55 dishes prepared by 51 restaurants in the city of Zurich showed that the average rösti contained 702 µg/kg acrylamide. By analysing the content of reducing sugars in the potatoes used for frying, it is shown that with simple measures, the exposure to acrylamide could easily be reduced by factor 2 or more, while even improving the culinary experience. Though rösti is a typical dish in the German-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Recent studies have reported that a fried potato dish as large contributor to acrylamide exposure [37]. Furthermore, acrylamide has been reported as a carcinogen showing hazardous effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that a fried potato dish as large contributor to acrylamide exposure [37]. Furthermore, acrylamide has been reported as a carcinogen showing hazardous effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…The mean AA contents in potato crisps prepared from different UK-grown potatoes ranged from 131 to 5,360 µg/kg ( 11 ). Rosti, a popular Swiss dish, made of grated and fried potatoes, contains an average of 702 µg/kg AA ( 12 ). The AA concentration in different commonly consumed breads ranges from <limit of quantification (LOQ) to 695 µg/kg, where the highest AA concentration was detected in wheat bran and whole wheat breads ( 13 ).…”
Section: Formation Of Aa In Food Productsmentioning
confidence: 99%
“…The rising acrylamide contents in food products is a huge concern to global food safety as well as to end-chain consumers (Vinci et al, 2012 ). Several reports depict the alarming levels (up to 70%) of acrylamide in food products that mainly come through the intake of fries, chips and other fried potato products (Pedreschi et al, 2014 ; McCombie et al, 2016 ; Esposito et al, 2017 ).…”
Section: Constrains To Potato Productivity and Qualitymentioning
confidence: 99%